An Examination of Factors Contributing to the Acceptance of Online Health Misinformation - Pan, Wenjing; Liu, Diyi; Fang, Jie (Frontiers in Psychology, 2021)
This study examined factors including health-related anxiety, preexisting misinformation beliefs, and repeated exposure contributing to individuals’ health misinformation acceptance. Through a large-scale online survey, this study found that health-related anxiety was positively associated with health misinformation acceptance. Preexisting misinformation beliefs, as well as repeated exposure to health misinformation, were both positively associated with health misinformation acceptance. The results also showed that demographic variables were significantly associated with health misinformation acceptance. In general, females accepted more health misinformation compared to males. Participants’ age was negatively associated with health misinformation acceptance. Participants’ education level and income were both negatively associated with their health misinformation acceptance.